Highly porous scaffolds of PEDOT:PSS for bone tissue engineering - Guex,A; Puetzer,J; Armgarth,A; Littmann,E; Stavrinidou,E; Gianellis,EP; Malliaras,GG; Stevens,MM (Acta Biomaterialia, 2017)
Conjugated polymers have been increasingly considered for the design of conductive materials in the field of regenerative medicine. However, optimal scaffold properties addressing the complexity of the desired tissue still need to be developed. The focus of this study lies in the development and evaluation of a conductive scaffold for bone tissue engineering. In this study PEDOT:PSS scaffolds were designed and evaluated in vitro using MC3T3-E1 osteogenic precursor cells, and the cells were assessed for distinct differentiation stages and the expression of an osteogenic phenotype.Ice-templated PEDOT:PSS scaffolds presented high pore interconnectivity with a median pore diameter of 53.6 ± 5.9 µm and a total pore surface area of 7.72 ± 1.7 m2·g−1. The electrical conductivity, based on I-V curves, was measured to be 140 µS·cm−1 with a reduced, but stable conductivity of 6.1 µS·cm−1 after 28 days in cell culture media. MC3T3-E1 gene expression levels of ALPL, COL1A1 and RUNX2 were significantly enhanced after 4 weeks, in line with increased extracellular matrix mineralisation, and osteocalcin deposition. These results demonstrate that a porous material, based purely on PEDOT:PSS, is suitable as a scaffold for bone tissue engineering and thus represents a promising candidate for regenerative medicine.